Innovative Development of Research Engagement Manual: Strategies to Enhance Recruitment and Retention of Black Individuals in Clinical Trials for Substance Use Disorders - Geoffrey Obel; DeWanda Harris-Trimiar; Joshua S. Elmore; Taryn L. Mayes; Adrienne Mays; Angela Casey-Willingham; Srividya Vasu; Steven Shoptaw; Madhukar H. Trivedi (Health Equity)
Background: The participation of Black individuals in clinical trials remains lower than that of other racial and ethnic groups. Substance abuse adds additional barriers to recruitment and retention. While significant attention has been devoted to identifying barriers to recruitment/retention, efforts have been largely unsuccessful in increasing the participation of Black individuals in clinical trials. This article details Phase 1 efforts to develop sustainable strategies to increase enrollment/recruitment of Black participants in clinical trials through an Innovative Development of Research Engagement Manual. Methods: Phase 1 involved a literature review and the establishment of an Expert Diversity Advisory Board, which identified barriers to Black individual participation in substance use disorder (SUD) research. Identified barriers included lack of awareness of research, mistrust, lack of comfort with research, lack of information, and time/resource constraints. Focus groups were conducted to assess the importance of the identified factors in 61 Black participants with SUD history. Results: Among the focus group participants, 37.7% indicated mistrust, 45.9% indicated a lack of knowledge, and 27.9% stated safety concerns as reasons for not engaging with researchers. They considered compensation, research benefits, study duration, privacy, safety, and side effects as vital information that informed their decisions on clinical trial participation. The focus groups identified financial incentives, potential treatment options, and potential for improved awareness about substance abuse treatment as factors that determine retention in a study. Conclusion: With barriers identified, future efforts will focus on qualitative assessments of focus group material and developing and evaluating the manual.